2006
DOI: 10.1002/macp.200500483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inorganic and Organic Salts on the Thermogelling Behavior of Poly(organophosphazenes)

Abstract: Summary: The effect of various inorganic (NaCl, KCl, NaBr, LiCl and NaI) and organic (Et4NBr, n‐Pr4NBr and n‐Bu4NBr) salts on the thermogelling behavior of poly(organophosphazenes) with α‐amino‐ω‐methoxy‐poly(ethylene glycol) (AMPEG) and amino acid ester side groups was studied. The salting‐out or salting‐in effects of inorganic salts were in good agreement with the so‐called “Hofmeister series”. In the presence of inorganic salts other than NaI, the association temperature (Tass) and the temperature at the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…A similar trend was reported by Cho, An, and Song 41 in their study of the effects of salts on the viscosity of polyorganophosphazenes. 41 As discussed earlier, the thermally induced gelation of HPMC solutions mainly involves hydrophobic association, which leads to a three-dimensional network. Therefore, gel strength is governed by the hydrophobic associations.…”
Section: Rheological Characterization On Heatingsupporting
confidence: 77%
“…A similar trend was reported by Cho, An, and Song 41 in their study of the effects of salts on the viscosity of polyorganophosphazenes. 41 As discussed earlier, the thermally induced gelation of HPMC solutions mainly involves hydrophobic association, which leads to a three-dimensional network. Therefore, gel strength is governed by the hydrophobic associations.…”
Section: Rheological Characterization On Heatingsupporting
confidence: 77%
“…However, this phenomenon must be more complicated because the magnitude of the salting-out effect depends on the nature of the polymer and salt as well as on the ionic strength and polymer concentration. The Hofmeister series sorts anions and cations of common salts by their relative salting-out efficiency in descending order [13,14,17]. Anions appear to have a greater influence than cations and their effects seem to be independent and additive [7,11,15,20].…”
Section: Introductionmentioning
confidence: 91%
“…Some electrolytes improve the solubility of linear nonionic polymers or the swelling ability of nonionic gels in aqueous media relative to pure water, which is called the salting-in effect [8,11,[14][15][16][17]21]. In general, salts inducing salting-in effects are expected to be at the end of the Hofmeister series but anti-Hofmeister behavior has also been reported for some gels [22].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As we know, addition of salts into electrospinning system can control fiber properties [22]. For example, the fiber will have some novel catalytic, optical, and magnetic properties by adding some salts [23][24][25]. It has been reported that highly porous nylon-6 fibers can be obtained by introducing salt [22] to the electrospinning system, but in this method, pores were still formed by selective dissolution of the salt in the as-spun fibers.…”
Section: Introductionmentioning
confidence: 95%